Radical Copolymerization and Charaterization of N-(Tri-n-Butyltin) Maleimide Monomer with Styrene, Methyl Methacrylate and N-Vinyl-2-Pyrrolidinone - S. Al-Muaikel, Nayef; S. Al-Diab, Salem; Z. Al-Khathlan, Hamed (Asian Journal of Chemistry, 2010)
Three types of novel organotin copolymers from polymerization of new organotin monomer N-(tri-n-butyltin) maleimide with styrene, methylmethacrylate and N-vinyl-2-pyrrolidinone in bulk at 65ºC. Using 2,2-azo bis isobutyro nitrile (AIBN) as initiator. Characterization of the prepared copolymers was accomplished by IR, 1H-NMR spectra and elemental analysis. All the copolymers dissolved radily at room temperature in most polar aprotic solvents. The thermal stability of the polymers was evaluated by TGA and DSC measurements.